Research on the problem of solar energy storage system based on AHP - Chai Xianyi; Zhu Yanqi; Qiu Lichuan; Cao Shenhui (E3S Web of Conferences, 2022)
Solar energy storage, while currently widely used as a clean and sustainable resource, is a critical issue that impacts the widespread use of solar energy technology. Using solar power to provide electricity can overcome the constraint of avoiding geography, which is crucial for the electricity problem associated with homes built in remote areas. However, it is limited by the sun’s irradiation. We should solve the electricity storage problem to support energy requirements at night and on a cloudy day. In our paper, we are tasked to evaluate the utility of battery storage system based on the energy needs and individual’s preferences. Considering individual’s needs and preferences, we proposed a generalized evaluation model based on AHP method. The method is based on the choice of variables that influence battery storage system section in question 1 and goes through a hierarchical analysis model to calculate the weights of variables. AHP method can effectively represent the preferences of individuals. Besides, we proposed a set of functions to evaluate the satisfaction of individual under each factor by considering individual’s expected cost and energy requirements. Finally, we talk about the future of cement batteries. The benefits and drawbacks of cement batteries as energy storage equipment are examined, focusing on cost, safety, and environmental contamination concerns. Furthermore, we assessed the future utility of cement battery in terms of cost, usable capacity, continuous power rating, instantaneous rower rating, lifetime of battery, and other factors.